Intensitas Perkataan Yesus Kristus di Kayu Salib dan Implikasinya bagi Pelayan Kristus - Marthen Mau; Henni Somantik (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
The intensity of Jesus Christ's statement when he was crucified is very urgent to continue to be studied, understood, and implied for today's servants of Jesus Christ. Servants of Jesus Christ must not stop teaching and preaching the statements of Jesus Christ when he was crucified to church members. Some people do not recognize the quality of the holy suffering experienced by Jesus Christ to save sinful humans, so they think that the one who was crucified on the cross was not Jesus Christ, but one of His disciples or someone else. This study aims to narrate the peak quality of the holy suffering of Jesus Christ through His words on the cross. Using a qualitative research method with a library research approach and grammatical studies to obtain research results, then analyzed based on biblical implications regarding the idea of ​​Jesus Christ experiencing suffering. In conclusion, through a grammatical analysis of biblical phenomena, the intensity of Jesus Christ's words on the cross must be understood from God's eternal plan for sinful humans.